Síntese e avaliação da atividade biológica de compostos N-Heterocíclicos - Sangi, Diego Pereira (Universidade Federal de São Carlos, 2011)
N-heterocyclic compounds have a large number of biochemical and medical applications and an important role in the discovery of new drugs, and many of best sellers, currently in use, contains one or more N-heterocyclic rings. Some classes of N-heterocyclic compounds are considered privileged scaffolds because the large spectrum of biological activities. In this work we developed a new microwave promoted synthesis of N,Sacetals and N-heterocycles, more specifically, benzoxazoles, oxazolines, hexahidropyrimidines and oxazinanes, starting from ketenedithioacetal. This new procedure allowed the synthesis of these compounds in shorter period of time when compared with other procedures described in the literature. A library of quinoxaline 2,3 disubstituted was synthesized, employing cross coupling reactions and also condensation of o-phenylenediamine and α-diketones. Biological activity of the quinoxalines 2,3-disubstituted was evaluated on the proliferation of promastigotes of Leishmania amazonensis and epimastigotes of Trypanosoma cruzi. Some of the synthesized quinoxalines showed good inhibition values at low concentrations. The anti-proliferative activity of the 2,3-diarylquinoxalines were also evaluated using MDA-MB231 and MCF-7 cells, however they showed no significant inhibition .
Keywords: Química orgânica; N-heterocíclicos; Síntese orgânica; CIENCIAS EXATAS E DA TERRA::QUIMICA